Analyses of Seven New Genomes of Xanthomonas citri pv. aurantifolii Strains, Causative Agents of Citrus Canker B and C, Show a Reduced Repertoire of Pathogenicity-Related Genes - Fonseca, Natasha Peixoto; Patané, José S. L.; Varani, Alessandro M.; Felestrino, Érica Barbosa; Caneschi, Washington Luiz; Sanchez, Angélica Bianchini; Cordeiro, Isabella Ferreira; Lemes, Camila Gracyelle de Carvalho; Assis, Renata de Almeida Barbosa; Garcia, Camila Carrião Machado; Belasque Jr., José; Martins Jr., Joaquim; et al. (Frontiers in Microbiology, 2019)
Xanthomonas citri pv. aurantifolii pathotype B (XauB) and pathotype C (XauC) are the causative agents respectively of citrus canker B and C, diseases of citrus plants related to the better-known citrus canker A, caused by Xanthomonas citri pv. citri. The study of the genomes of strains of these related bacterial species has the potential to bring new understanding to the molecular basis of citrus canker as well as their evolutionary history. Up to now only one genome sequence of XauB and only one genome sequence of XauC have been available, both in draft status. Here we present two new genome sequences of XauB (both complete) and five new genome sequences of XauC (two complete). A phylogenomic analysis of these seven genome sequences along with 24 other related Xanthomonas genomes showed that there are two distinct and well-supported major clades, the XauB and XauC clade and the Xanthomonas citri pv. citri clade. An analysis of 62 Type III Secretion System effector genes showed that there are 42 effectors with variable presence/absence or pseudogene status among the 31 genomes analyzed. A comparative analysis of secretion-system and surface-structure genes showed that the XauB and XauC genomes lack several key genes in pathogenicity-related subsystems. These subsystems, the Types I and IV Secretion Systems, and the Type IV pilus, therefore emerge as important ones in helping explain the aggressiveness of the A type of citrus canker and its apparent dominance in the field over the B and C strains.